MATEC Web of Conferences - Khaustov, S. A. specialist in the field of power engineering Assistant of the Department of Tomsk Polytechnic University, Engineer 1988- (EDP Sciences, 2018)
The paper presents ordinary differential equations for the dynamic characteristics of a solid fuel boiler that can be combined into one-dimensional nonstationary mathematical model for simulating long-term dynamics of a solid fuel boiler. This model requires less computational time for a qualitative simulation of boiler's operation than known CFD-solutions. The long-term dynamic model presented can help to determine annual costs, to set up automatic control systems and to detect dangerous deviations in the project.